2007
DOI: 10.1161/01.str.0000259657.73682.03
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Linkage Analyses Confirm Chromosome 19q13.3 as a Susceptibility Locus for Intracranial Aneurysm

Abstract: Background and Purpose-In previous studies of familial intracranial aneurysm (IA), parametric linkage analyses have been undertaken for five unrelated families, four providing maximum logarithm of odds (LOD) scores with dominant models and one with a recessive model. Each family was linked to a distinct locus, indicating locus heterogeneity. This study aimed to examine whether Japanese IA families consistent with autosomal-dominant mode of inheritance support linkage to these loci. Methods-We performed genomew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 42 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Nonparametric linkage analysis revealed 3 loci located on 17cent, 19q13, and Xp22, 6 and parametric analysis revealed a locus on 19q13. 7 On 17cent, we found TNFRSF13B to be a candidate gene for IA. 8 Several other studies have revealed several loci or candidate genes in different populations.…”
mentioning
confidence: 84%
“…Nonparametric linkage analysis revealed 3 loci located on 17cent, 19q13, and Xp22, 6 and parametric analysis revealed a locus on 19q13. 7 On 17cent, we found TNFRSF13B to be a candidate gene for IA. 8 Several other studies have revealed several loci or candidate genes in different populations.…”
mentioning
confidence: 84%
“…So far, different genome-wide linkage studies have identified several loci [44], but only four (p4.-p6., 7q, 9q. and Xp22) have been replicated in different populations [75,246,259,28,284,45,420,49]. Knowledge on the genetic determinants may provide insight into the development of aneurysms, and thereby give clues on how to stop aneurysm formation.…”
Section: Genetics Of Intracranial Aneurysmsmentioning
confidence: 99%
“…Hand searching of reference lists of identified articles was also carried out. We identified eight whole-genome scans between the years 2001 and 2007 [3][4][5][6][7][8][9][10]. Studies included in our analysis all assessed the linkage of autosomal genome sites with familial intracranial aneurysm.…”
Section: Selection Of Genome Scans and Data Collectionmentioning
confidence: 99%
“…We did not consider the second stage of scans where candidate regions from the first stage were fine mapped. One study was excluded because data from affected individuals had already been included in a previous report [3]. Where studies failed to present sufficient data for analysis the information was requested from the corresponding authors.…”
Section: Selection Of Genome Scans and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation